MALAYSIA AND MAHATHIR IN THE GLOBAL CHALLENGE - Sigit Sigit (Verity: Jurnal Ilmiah Hubungan Internasional (International Relations Journal), 2020)
The aim of this study is to analyze Mahathir’s policy through a historical approach to the political developments and challenges in Malaysia. In addition, the author uses secondary data in order to collect several resources related to the topic. The comeback of Mahathir Mohammad, the Father of Malaysian modernization, in the Malaysian 14th general election after leaving the political stage for more than a decade draws many global eyes. As the great critics of the corruption and downturn of Malaysian economic conditions, he decided to run in Malaysia once again. During his previous administration, his mega-project named Pembangunan Putra Jaya and his famous foreign policy “Look East Policy” became a part of his identity. The “Look East Policy” was developed in order to increase domestic economic growth and because Malaysia needed to learn and adopt cultural features from Japan and Korea, such as discipline and hard work. Through this policy, Malaysia began cooperating with East countries (Japan and Korea). In addition, Mahathir had been opposing Western values and deemed them incompatible with Asia. The West considers Mahathir to be an obstacle in uniting Western and Asian countries following the emergence of Asian values since the 1990s. Overall, this study suggests that Mahathir is only focused on his country’s national interest and sovereignty and maintaining Malaysia’s international standing.Bahasa Indonesia Abstract: Tujuan paper ini adalah untuk menganalisis kebijakan Mahathir melalui perspektif sejarah terhadap perkembangan politik dan tantangan di Malaysia. Selain itu, Penulis menggunakan data sekunder untuk mengumpulkan berbagai literatur terkait dengan topik tersebut. Kembalinya Mahathir Muhammad, Bapak Modernisasi Malaysia, dalam Pemilihan Umum ke-14 setelah meninggalkan panggung politik lebih dari satu dekade telah menarik perhatian masyarakat global. Sebagai kritikus pada korupsi dan kemunduran ekonomi Malaysia, dia memutuskan untuk maju dalam pemilihan umum sekali lagi. Selama pemerintahan sebelumnya, Mahathir dengan proyek megah yaitu Pembangunan Putra Jaya dan kebijakan luar negerinya, terkenal dengan  “Look East Policy” menjadi bagian dari identitasnya.  Kebijakan “Look East Policy” dikembangkan untuk meningkatkan pertumbuhan ekonomi domestik dan karena Malaysia perlu belajar dan mengadopsi budaya dari Jepang dan Korea, seperti kedisiplinan dan kerja keras. Melalui Kebijakan tersebut, Malaysia telah melakukan kerjasama dengan negara Timur (Jepang dan Korea). Selain itu, Mahathir menolak penerapan nilai-nilai Barat dan menganggap bahwa nilai Barat tidak sesuai dengan Asia. Negara-negara Barat menganggap Mahathir sebagai penghalang persatuan negara Barat dengan negara Asia sejak berkembangnya paham “Asian Values” pada tahun 1990an. Secara Keseluruhan, paper ini berpendapat bahwa Mahathir hanya fokus kepada kepentingan dan kedaulatan negaranya dan menjaga eksistensi Malaysia di dunia internasional.